Kemitraan Suami Istri Perspektif Hukum Keluarga Islam dan Implementasinya pada Anggota Jama'ah Tabligh Medan Amplas - Muhammad Royhan; Sukiati Sukiati (LPPM Universitas Ekasakti Padang, 2023)
The Tablighi congregation often carries out its da'wah activities by leaving his wife, who is called khuruj. Ideally, in Islamic law, a partnership must be built to form a family, what happens in a family but the husband only preaches outside (khuruj), giving the impression that he does not take care of the household. A husband and wife partnership is built on the relationship between husband and wife in building a household to achieve common goals. This study aims to examine the relationship between husband and wife in the Tablighi congregation family, especially in the Medan Amplas Tablighi congregation family. This study is also to analyze the partnership that is built within the family from the perspective of Islamic Family law. Using qualitative methods, data was explored using interviews. This study found that basically a good and harmonious family is a commandment in Islamic teachings. Then from the thoughts above the question arises, what is the actual relationship between husband and wife among the tabligh congregation. Do they really have an ideal partnership as suggested by Islam? What about their partnership from a gender perspective? Why is it necessary to look at it from a gender perspective because the relationship between husband and wife is always related to gender, is that true? The purpose of this writing is to determine the suitability of Islamic family law and its implementation for husband and wife partnerships among members of the Medan Amplas tabligh congregation. The research methods used are library research and field research. The results of this research are that the husband and wife partnership built by the Medan Amplas tabligh congregation family is very organized following the procedures taught by the Prophet and according to Islamic law.